RESPONS PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS SORGUM (Sorghum bicolor (L.) Moench) DENGAN PERBEDAAN SISTEM PENGOLAHAN TANAH - Leonard Septian Munthe1*, Leonard Septian Munthe1*, Leonard Septian Munthe1*,; T. Irmansyah T. Irmansyah; Chairani Hanum (Universitas Sumatera Utara, 2013)
Growth and Yield Response of Three Sorghum Varieties (Sorghum bicolor (L.) Moench) onDifferent Soil Tillage. The aim of this research was to compare growth and yield of three varieties ofsorghum on different soil tillage. It was conducted at Pasar 1, Tanjung Sari, Medan about 25 mabove sea level on June to October 2012 by using Split Plot Design with two factors. The first factorwas sorghum variety (Sangkur, Kawali, Numbu) and the second one were different soil tillage (notillage, once tillage, twice tillage). The research land had sandy loam soil texture. The results ofresearch showed that growth and yield of Sangkur, Kawali, and Numbu weren’t effected by soiltillage treatment but without tillage treatment showed the best result. Numbu had better result onshoot dry weight (59.29%), biomass weight (59.37%), root volume (64.83%), yield per sample(59.42%), and 1000 grains weight (56.83%) compared with other varieties. The interaction betweensorghum variety and different soil tillage had no significantly effect on growth and yield of sorghum.Key words : Sorghum, variety, soil tillage, growth, yield